Cardiopericardial wounds - Gregorio, Luis A (Cirugía del Uruguay, 1973)
The symptoms of cardio-pericardial wounds are extremely varied; Between the classic clinical form of cardiac tamponade to the absolutely inapparent forms, there is a wide range of symptoms that the clinician and fundamentally the general surgeon, who is the one who ultimately must assume maximum responsibility, must know in depth in order to reach a diagnosis. accurate.